Spatiotemporal Variations in the Air Freezing and Thawing Index Over the Mongolian Plateau From 1901 to 2019 - Ma, Xin; Wu, Tonghua; Zhu, Xiaofan; Lou, Peiqing; Wang, Dong; Adiya, Saruulzaya; Avirmed, Dashtseren; Dorjgotov, Battogtokh; Chen, Jie; Shang, Chengpeng; Wen, Amin; La, Yune; et al. (Frontiers in Environmental Science, 2022)
The Mongolian Plateau is located in the permafrost transitional zone between high-altitudinal and high-latitudinal permafrost regions in the Northern Hemisphere. Current knowledge of the thermal state and changes in the permafrost on the Mongolian Plateau is limited. This study adopted an improved calculation method of the Mongolian Plateau air freezing and thawing index using the monthly air temperature reanalysis dataset from Climate Research Unit (CRU). The spatial and temporal variation characteristics from 1901 to 2019 were further assessed by the Mann-Kendall (M-K) test and spatial interpolation methods. The results indicate that the spatial distribution of the freezing and thawing index shows clear latitudinal zonality. Over the study period, the air freezing index decreased by 4.1 ℃·d/yr, and the air thawing index has increased by 2.3 ℃·d/yr. The change-point in the air thawing index appeared in 1995 (P<0.05) based on the M-K method, in contrast to the so-called hiatus in global warming. Our results reveal rapid warming on the Mongolian Plateau, especially in the permafrost region, and are useful for studying permafrost changes on the Mongolian Plateau.